Assessing the Stabilization of Laterite Soils Using Steel Slag and Quarry Dust for Road Subbase Layer - Elvis Ssekkalaba (Uganda Christian University, 2025)
Lateritic soils are often weak and unsuitable for road construction without stabilisation. This study assesses the suitability of stabilising lateritic soil using steel slag and quarry dust, focusing on the Nasuuti-Nakabago-Ntawo road, where soil from the Nsambwe borrow pit had a CBR of 24.7 %, below the required 45 % for a G45 granular subbase material. Proctor test, CBR, Atterberg limits, and particle size distribution, were performed on varying percentages of laterite, steel slag, and quarry dust. The results showed that 40 % steel slag addition increased the CBR by 160 % and reduced CBR swell by 70 %, improving load-bearing capacity. 10 % quarry dust with 40 % steel slag effectively reduced the plasticity index by 27 %, liquid limit by 13 %, and linear shrinkage by 33 %, enhancing workability and durability. These findings confirm that a combination of steel slag and quarry dust can significantly improve laterite soil properties, making it suitable for subbase applications in road construction.
Undergraduate